Partial exchange transfusion to prevent neurodevelopmental disability in infants with polycythemia. - (:unkn) unknown (My University, 2010)
BACKGROUND: Hyperviscosity of blood results in increased resistance to blood flow and decreased oxygen delivery. In the neonate, hyperviscosity can cause abnormalities of central nervous system function, hypoglycemia, decreased renal function, cardiorespiratory distress, and coagulation disorders. Hyperviscosity has been reported to be associated with long-term motor and cognitive neurodevelopmental disorders. Blood viscosity exponentially increases when an infant has polycythemia (hematocrit >/= 65%). Partial exchange transfusion (PET) is traditionally used as the method to lower the hematocrit and treat hyperviscosity. OBJECTIVES: To evaluate the effect of PET on mortality and neurodevelopmental outcome in infants with neonatal polycythemia. SEARCH STRATEGY: Electronic databases searched included: The Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), MEDLINE (1966 to October 2009), EMBASE (1980 to October 2009) and CINAHL (1982 to October 2009). SELECTION CRITERIA: Randomized controlled clinical trials or quasi-randomized trials comparing partial exchange transfusion to control (non-treatment) in infants with neonatal polycythemia DATA COLLECTION AND ANALYSIS: Data collection and analysis was performed according to the standards of the Cochrane Neonatal Review Group. MAIN RESULTS: One study (Kumar 2004) reported no demonstrable effect on the risk of neonatal mortality (RR 5.23, 95% CI 0.66, 41.26).Four studies reported on neurodevelopmental assessment at 18 months or older. The completeness of follow-up differed widely between the studies. Overall, no difference was seen in developmental delay when all trials are analysed based on available cases (typical RR 1.45, 95% CI 0.83 to 2.54) and when only the randomized controlled trials are analysed (typical RR 1.35, 95% CI 0.68 to 2.69). A best case/worst case analysis of developmental delay is consistent with large benefit or harm from PET.Two studies reported on necrotizing enterocolitis (Van der Elst 1980; Black 1985). An increase in the risk of NEC was noted in infants receiving PET (typical RR 11.18, 95% CI 1.49, 83.64; typical RD 0.14, 95% CI 0.05, 0.22). No differences in short-term complications including hypoglycemia (two studies) and thrombocytopenia (one study) were noted. AUTHORS' CONCLUSIONS: There are no proven clinically significant short or long-term benefits of PET in polycythemic newborn infants who are clinically well or who have minor symptoms related to hyperviscosity. PET may lead to an increase in the risk of NEC. The data regarding developmental follow-up is extremely imprecise due to the large number of surviving infants who were not assessed and, therefore, the true risks and benefits of PET are unclear.